Sustainability Disparities Between Local and Multinational Companies in Iraq: Kesenjangan Keberlanjutan Antara Perusahaan Lokal dan Multinasional di Irak - Layla Mansour Mazhar; Readh Najem Obaid (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Sustainability has become a critical focus in corporate governance, influencing business policies and operational strategies worldwide. In developing economies like Iraq, integrating sustainability remains challenging due to regulatory limitations, financial constraints, and infrastructural barriers. Specific Background: The oil and gas, agriculture, and manufacturing sectors are pivotal to Iraq’s economy, yet they exhibit varying degrees of sustainability adoption. While multinational corporations demonstrate advanced sustainability practices, local firms struggle with compliance and resource limitations. Knowledge Gap: Existing research on corporate sustainability in Iraq remains scarce, particularly regarding sectoral differences and the influence of international firms in shaping sustainability standards. Aims: This study analyzes the effects of sustainability policies on companies in Iraq, comparing local and multinational firms across key industries to assess their sustainability practices, challenges, and compliance levels. Results: Findings indicate that multinational corporations lead in sustainability implementation, particularly in energy efficiency and corporate social responsibility (CSR). Local companies face regulatory and financial constraints but are progressively integrating CSR initiatives. Compared to the broader Middle East, Iraqi firms exhibit lower sustainability adoption due to weaker regulations and reduced public scrutiny. Employees in multinational firms report higher engagement with sustainability policies than those in local firms. Novelty: This study provides a comparative analysis of sustainability practices in Iraq and the Middle East, highlighting disparities in renewable energy usage, CSR initiatives, and employee perceptions. It also identifies barriers hindering local companies from adopting sustainable practices. Implications: Strengthening environmental regulations, increasing public awareness, and providing financial incentives for renewable energy adoption are essential for enhancing corporate sustainability in Iraq. The findings offer policymakers and business leaders strategic insights into improving sustainability frameworks and aligning corporate practices with global standards. Future research should explore policy interventions and their impact on corporate sustainability performance in Iraq. Highlights Iraqi companies lag in sustainability due to weak regulations and funding. Multinational firms lead; local firms struggle with compliance and capital. Strengthening laws, public awareness, and subsidies can enhance sustainability. Keywords: Sustainability, Corporate Policies, Environmental Protection, Corporate Social Responsibility.